جهود ابن عاشور في الإصلاح التربوي من خلال تفسيره سورة يوسف أنموذجا = The contribution of Ibn ‘Āshūr in educational reform in his tafsir the case of Surah Yūsuf - Elatrash, Radwan Jamal Yousef; Abdo Khaled, Nashwan; Ali A Mohamed, Azaldien (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يركز هذا البحث على إظهار جهود ابن عاشور في الإصلاح التربوي من خلال كتابه التحرير والتنوير، والناظر في تفسير ابن عاشور يجده ثرياً بالقضايا التربوية، لهذا يُعد ابن عاشور من أهم من أسهموا بالفكر الإصلاحية التربوية، و في هذا الإطار جاء هذا البحث لإبراز بعض من تلك القضايا الإصلاحية، من خلال التركيز على سورة واحدة وهي سورة يوسف، إذْ أن هذه السورة تتضمن العديد من القضايا التربوية العظيمة التي نحتاج إليها في إصلاح ما اعترى مجتمعاتنا من خلل، ولما تمثله من مرتكز إصلاحي أساسي، وطبيعة البحث تحتاج منا أن نستخدم المنهج الاستقرائي، وهو استقراء القضايا التربوية التي أشار إليها ابن عاشور في تفسيره لسورة يوسف، ومن ثمّ تحليليها ودراسة طرق الاستفادة منها في حياتنا العملية، ومن أهم النتائج: أثبت البحث أن تفسير التحرير والتنوير مليء بالقضايا التربوية وخاصة القضايا التي تعرضت لها سورة يوسف، القضية الأولى: العلاقة القوية التي تربط الأب يعقوب  بابنه يوسف  وكيف نستفيد منها في تقوية العلاقة الأسرية، القضية الثانية: الحسد بين الإخوة الذي يصيب كثيراً من الأسر، وكيف عالج يعقوب  ذلك. ******************************************************** The study focuses on the efforts of Ibn ‘Āshūr in the educational reform through his book “Interpretation of verification and enlightenment”. Any researcher reads the interpretation of Ibn Ashour would find that it is rich in educational issues; therefore, Ibn ‘Āshūr is one of the most important contributors to the educational reformist thought. In this context, this study highlights some of these reform issues by focusing on Sūrah Yūsuf, as its verses contains many of the educational subjects that we need in solving the problems that have affected our society, and because the Surah represents a fundamental reform framework. The inductive method was used in this study to extrapolate the educational issues raised by Ibn Ashour in his interpretation of Sūrah Yūsuf, and then analyse them and study how to benefit from his book in our practical daily life. One of the most important findings of this study is that the interpretation of verification and enlightenment is full of educational issues, especially the issues that have been clarified by Sūrah Yūsuf. The first issue is the strong relationship between Father Jacob (Ya’qūb) and his son Joseph (Yūsuf) peace be upon them and how to benefit from it in strengthening the family relationship, the second issue is the envy among brothers which infects many families, and how Jacob solved that problem.